Trace elements, anions, and carbohydrates in the recirculating aquaculture system using woodchip denitrification, constructed wetland, and sand infiltration - Lindholm-Lehto, Petra Camilla; Lindroos, Antti-Jussi; Pulkkinen, Jani Tapio; Kiuru, Tapio; Vielma, Jouni (IWA Publishing, 2022)
A recirculating aquaculture system (RAS) aims to achieve fish production with negligible discharge into the environment. RASs have been applied for fish production in several countries, but nitrate removal is often a limiting factor for production increases. In this study, a pilot-scale RAS (10 tons of fish/year) was connected to a water treatment field which consisted of a denitrifying woodchip bioreactor (9 m × 14 m) filled with birch woodchips (Betula pendula), a constructed wetland (7.5 m × 6 m), and sand infiltration (16 m × 31 m) to achieve high water quality with low-maintenance treatment units. In the constructed wetland, a perennial common reed (Phragmites australis) was used in a well-drained soil for nutrient re-use. Concentrations of different elements, diluted anions, and selected hydrocarbons were monitored and quantified. Some Mn leaching occurred during the sand infiltration stage. However, Mn concentrations decreased towards the end of the experiment. Concentrations of total-Fe increased up to 2.75 mg L−1 and Mn up to 5 mg L−1 in the sand infiltration stage of the water treatment field, probably due to anoxic conditions and leaching of fine particles. This type of process design offers effective but low-maintenance treatment of circulating water.
Keywords: constructed wetland; denitrification; heavy metals; recirculating aquaculture system (RAS); sand infiltration; woodchip bioreactor